A study on relationship between organizational culture and organizational commitment - Maryam Khalili (Management Science Letters)
This paper presents an empirical investigation to study the relationship between organizational culture and organization commitment. The study uses two questionnaires, one for measuring organizational commitment originally developed by Meyer and Allen (1991) [Meyer, J. P., & Allen, N. J. (1991). A three-component conceptualization of organizational commitment. Human resource management review, 1(1), 61-89.] and the other one for organizational culture developed by Denison and Spreitzer (1991) [Denison, D. R., & Spreitzer, G. M. (1991). Organizational culture and organizational development: A competing values approach. Research in organizational change and development, 5(1), 1-21.]. The study is accomplished among selected full time employees who work for an Iranian bank named Bank Saderat Iran. Using Pearson correlation test as well as linear regression methods, the study has determined that there were some positive and meaningful relationship between all components of organizational commitment and organizational culture.